2023
DOI: 10.3390/en16155778
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of a Grid-Connected Distributed Wind Turbine

Abstract: The utilization of wind energy has become increasingly popular in the United States and many European countries due to its abundant nature and optimized design. While existing wind turbines are predominantly large-scale and not suitable for standalone or distributed power production, Lubbock County in West Texas offers a diverse range of renewable energy options to meet its energy needs. The region relies heavily on utility-scale wind energy sources to supply power to the Texas Grid, replacing conventional fos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Small to medium vertical axis wind turbines are reported as the best choice for wind power generation in port buildings of Alexandria, Egypt [94]. A case study in Lubbock, USA, showed that the city has great potential to generate wind power with a wind speed of 11.6 m/s, and 6 kW distributed wind turbines can reduce greenhouse gas emissions by 50% annually [95]. From a case study on wind turbines in building tunnels in a Chinese city, it was reported that the Savonius rotor installed in a duct attained higher performance than the free stream rotor [98].…”
Section: Brussels Belgiummentioning
confidence: 99%
“…Small to medium vertical axis wind turbines are reported as the best choice for wind power generation in port buildings of Alexandria, Egypt [94]. A case study in Lubbock, USA, showed that the city has great potential to generate wind power with a wind speed of 11.6 m/s, and 6 kW distributed wind turbines can reduce greenhouse gas emissions by 50% annually [95]. From a case study on wind turbines in building tunnels in a Chinese city, it was reported that the Savonius rotor installed in a duct attained higher performance than the free stream rotor [98].…”
Section: Brussels Belgiummentioning
confidence: 99%
“…CO 2 Reduction = Baseline Emissions − Microgrid Emissions (24) In the endeavor to propose a grid-connected microgrid solution, several critical aspects and input parameters have been carefully considered as shown in Table 1. The microgrid's anticipated same load profile, outage frequency, average outage duration, and lifetime is set at 20 years, with a discount rate of 5% and an inflation rate of 2% accounted for in financial evaluations.…”
Section: Simple Payback =mentioning
confidence: 99%
“…Accurate solar irradiance prediction is critical for optimizing the utilization of renewable energy sources, while load forecasting facilitates the efficient allocation of energy resources [2,3,22]. The LSTM model's innate ability to capture temporal dependencies within data significantly improves upon traditional methods, leading to heightened forecasting accuracy [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, renewable energy sources present an ideal solution for addressing the surging demand while generating zero-carbon emissions. Furthermore, recent advancements in control approaches for renewable energy sources, particularly solar and wind sources, have facilitated the seamless integration of these renewable sources into the preexisting power networks [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%